Evaluation of Semen Quality and Estimation of Semen Repeatability Value of Madura Bulls at Lembang Artificial Insemination Center - Wigiyanti, Ema Trie; Indrijani, Heni; Darodjah, Siti; Kurnia, Asep (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Madura bull are one of the local bulls in Indonesia whose semen is used for artificial insemination. This study aims to evaluate the quality of semen and the repeatability value of semen from Madura bulls at the Lembang Artificial Insemination Center. A total of 1,402 semen collection data from three Madura bulls from 2014-2020 were used for analysis. The data was analyzed descriptively to evaluate semen quality consisting of semen volume, sperm motility and sperm concentration. Repeatability value was estimated using analysis of variance and intra-class correlation. The results showed that the average volume, motility, and concentration were 5.32 ± 1.50 ml; 68.10±7.07 %; and 1,044.27 ± 277.63 million/ml. The semen volume repeatability value was high, motility was low, and concentration was medium.